Access to higher education: ProUni in focus - Vera Lucia Felicetti; Alberto F. Cabrera (Education Policy Analysis Archives, 2018)
The focus of this article is the access to Higher Education in Brazil and the University for All Program (ProUni). The research aimed to understand if ProUni is complying with its objective of creating opportunities to students from vulnerable groups for accessing Higher Education, and if there are differences in the baseline characteristics of ProUni graduates and non-ProUni graduates when admitted in a Higher Education. Using a quantitative approach with explanatory goal, data were analyzed via descriptive and inference statistics. Survey participants included 57 ProUni and 140 non-ProUni graduates; all were already Higher Education graduates from a non-profit institution in Southern Brazil and had accessed this level of education in 2005. The results show that ProUni provided access to Higher Education to a younger group of students than the non-ProUni group. The ProUni group also contained a larger number of women and a higher proportion of non-whites than the other group. Among ProUni scholarships, 12.28% had a per capita income higher monthly to three minimum wages and had a higher probability of choosing a licentiate/undergraduate degree. The graduates of the non-ProUni group tended to be more motivated by intrinsic factors, while the ProUni group is motivated by extrinsic factors when choosing courses.